Strategic plan for algarveresorts internationalization process to Florida, USA. - Bispo, Bernardo Jerónimo (2016)
Tourism is a volatile industry where a slight change in politics, economics or a natural catastrophe can change the game rules overnight. Geographic diversity is a key factor to create a solid company structure in tourism industry. Operating in different locations, dealing with diverse markets, decrease business dependency in geography. With lower risk, companies are free to focus on optimizing their local and daily services management. The following dissertation intends to be a business plan focused on Algarveresorts’ internationalization process. This plan consists in a business expansion for Algarveresorts to the United States of America, specifically to the Florida State. This process of internationalization aims to reduce the business risk related to the fact that the company operates solo in one geographic location, which makes Algarveresort completely dependent on a single market in all it’s operations. The firm aims to expand it’s business as well as building a solid and versatile company structure. With the internationalization process, the firm intends to grow in the tourism sector internationally. Throughout the development and results measurement on this strategic plan it is easy to say that Florida is teeming with opportunities for the whole process of expansion and internationalization of Algarveresorts. As well as the final projected model fulfill all the company expectations and aims, being completely in the reach of Algarveresorts resources. Although the huge and strong competition in that market it is safe to say that Florida can surely become the next market to be explored by the Company.